ANALYSIS OF WAITING TIME FOR OUTPATIENT SERVICES AT MITRA SEJATI HOSPITAL MEDAN - Andika, Wulan; Fanisa, Siti; Sabila, Farah; Pasaribu, Riska Fadilla; Ningrum, Tiara Pakar; Lestari, Anisa Ayu; Agustina, Dewi (HEARTY, 2025)
Waiting time is the time used by patients to get health services from the registration point to entering the doctor’s examination room. The length of patient waiting time is one of the important things in determining the quality of health services. This study aims to analyze the length of waiting time (arrival process, service, human resources. This study uses a qualitative method with a descriptive approach. Data collection with this study was carried out using in-depth interview techniques and collation methods with observation. The registration process is still lacking because the Hospital still uses manual methods and the use of SIMRS has not been fully implemented. The number of human resources is still lacking, the outpatient waiting time is not up to standard because it exceeds 60 minutes, the availability of facilities and infrastructure is still lacking such as computers, signals. Other factors that cause long patient waiting times and examination results are not yet connected to all units so that it takes a long time.